Climate effects on US infrastructure: the economics of adaptation for rail, roads, and coastal development - James E. Neumann; Paul Chinowsky; Jacob Helman; Margaret Black; Charles Fant; Kenneth Strzepek; Jeremy Martinich (Climatic Change, 2021)
Changes in temperature, precipitation, sea level, and coastal storms will likely increase the vulnerability of infrastructure across the USA. Using models that analyze vulnerability, impacts, and adaptation, this paper estimates impacts to railroad, roads, and coastal properties under three infrastructure management response scenarios: No Adaptation; Reactive Adaptation, and Proactive Adaptation. Comparing damages under each of these potential responses provides strong support for facilitating effective adaptation in these three sectors. Under a high greenhouse gas emissions scenario and without adaptation, overall costs are projected to range in the $100s of billions annually by the end of this century. The first (reactive) tier of adaptation action, however, reduces costs by a factor of 10, and the second (proactive) tier reduces total costs across all three sectors to the low $10s of billions annually. For the rail and road sectors, estimated costs for Reactive and Proactive Adaptation scenarios capture a broader share of potential impacts, including selected indirect costs to rail and road users, and so are consistently about a factor of 2 higher than prior estimates. The results highlight the importance of considering climate risks in infrastructure planning and management.

Climate change and developing country growth: the cases of Malawi, Mozambique, and Zambia - Channing Arndt; Paul Chinowsky; Charles Fant; Sergey Paltsev; C. Adam Schlosser; Kenneth Strzepek; Finn Tarp; James Thurlow (Climatic Change, 2019)

An uncertainty approach to assessment of climate change impacts on the Zambezi River Basin - Charles Fant; Yohannes Gebretsadik; Alyssa McCluskey; Kenneth Strzepek (Climatic Change, 2015)

Regional climate change of the greater Zambezi River Basin: a hybrid assessment - C. Adam Schlosser; Kenneth Strzepek (Climatic Change, 2015)

Informed selection of future climates - Channing Arndt; Charles Fant; Sherman Robinson; Kenneth Strzepek (Climatic Change, 2015)
Analysis of climate change is often computationally burdensome. Here, we present an approach for intelligently selecting a sample of climates from a population of 6800 climates designed to represent the full distribution of likely climate outcomes out to 2050 for the Zambeze River Valley. Philosophically, our approach draws upon information theory. Technically, our approach draws upon the numerical integration literature and recent applications of Gaussian quadrature sampling. In our approach, future climates in the Zambeze River Valley are summarized in 12 variables. Weighted Gaussian quadrature samples containing approximately 400 climates are then obtained using the information from these 12 variables. Specifically, the moments of the 12 summary variables in the samples, out to order three, are obliged to equal (or be close to) the moments of the population of 6800 climates. Runoff in the Zambeze River Valley is then estimated for 2026 to 2050 using the CliRun model for all 6800 climates. It is then straightforward to compare the properties of various subsamples. Based on a root of mean square error (RMSE) criteria, the Gaussian quadrature samples substantially outperform random samples of the same size in the prediction of annual average runoff from 2026 to 2050. Relative to random samples, Gaussian quadrature samples tend to perform best when climate change effects are stronger. We conclude that, when properly employed, Gaussian quadrature samples provide an efficient and tractable way to treat climate uncertainty in biophysical and economic models.

Economic impacts of climate change on water resources in the coterminous United States - James Henderson; Charles Rodgers; Russell Jones; Joel Smith; Kenneth Strzepek; Jeremy Martinich (Mitigation and Adaptation Strategies for Global Change, 2015)

Climate change impacts on freshwater recreational fishing in the United States - Russell Jones; Constance Travers; Charles Rodgers; Brian Lazar; Eric English; Joshua Lipton; Jason Vogel; Kenneth Strzepek; Jeremy Martinich (Mitigation and Adaptation Strategies for Global Change, 2013)

Climate change adaptation advantage for African road infrastructure - Paul Chinowsky; Amy Schweikert; Niko Strzepek; Kyle Manahan; Kenneth Strzepek; C. Adam Schlosser (Climatic Change, 2013)

Estimated effects of climate change on flood vulnerability of U.S. bridges - Len Wright; Paul Chinowsky; Kenneth Strzepek; Russell Jones; Richard Streeter; Joel B. Smith; Jean-Marc Mayotte; Anthony Powell; Lesley Jantarasami; William Perkins (Mitigation and Adaptation Strategies for Global Change, 2012)

Coping with climate variability and climate change in La Ceiba, Honduras - Joel B. Smith; Kenneth M. Strzepek; Julio Cardini; Mario Castaneda; Julie Holland; Carlos Quiroz; Tom M. L. Wigley; Jose Herrero; Peter Hearne; John Furlow (Climatic Change, 2011)

Adaptation and mitigation as complementary tools for reducing the risk of climate impacts - Gary Yohe; Kenneth Strzepek (Mitigation and Adaptation Strategies for Global Change, 2007)

Modeling the potential effects of climate change on water temperature downstream of a shallow reservoir, lower madison river, MT - Michale N. Gooseff; Kenneth Strzepek; Steven C. Chapra (Climatic Change, 2005)

Global Analysis of Changes in Water Supply Yields and Costs under Climate Change: A Case Study in China - Paul Kirshen; Mark McCluskey; Richard Vogel; Kenneth Strzepek (Climatic Change, 2005)

Responses and Thresholds of the Egyptian Economy to Climate Change Impacts on the Water Resources of the Nile River - Kenneth M. Strzepek; David N. Yates (Climatic Change, 2000)

An Assessment of Integrated Climate Change Impacts on the Agricultural Economy of Egypt - David N. Yates; Kenneth M. Strzepek (Climatic Change, 1998)

CLIMATE CHANGE IMPACTS ON THE HYDROLOGIC RESOURCES OF EUROPE: A SIMPLIFIED CONTINENTAL SCALE ANALYSIS - Kenneth M. Strzepek; David N. Yates (Climatic Change, 1997)